Development of Novel Antimicrobial Dental Composite Resin with Nano Cerium Oxide Fillers - Varghese, Eldho Jijy; Sihivahanan, Dhanasekaran; Venkatesh, Kondas Vijay (International Journal of Biomaterials, 2022)
Objectives. To assess the antibacterial efficacy of experimental dental composite resin with cerium oxide nanoparticles as fillers. Methods. The cerium oxide nanoparticles were prepared by the coprecipitation procedure. Synthesized 3wt% CeO2 nanoparticles were added to the composite resin as antibacterial filler. Experimental composite resin was manually prepared by adding ingredients. The resin matrix consisted of two mixed monomers, bisphenol A-glycidyl methacrylate and triethylene glycol dimethacrylate, diketone as the photo initiator, and N, N-dimethylaminoethyl methacrylate as a coinitiator. The antibacterial efficacy against Streptococcus mutans, Streptococcus mitis, Streptococcus aureus, and Lactobacillus spp. bacterial strains was tested using the microdilution method keeping commercially available 3M Filtek Z250 restorative composite as control. Results. The experimental dental composite demonstrated 99.503% efficacy against Streptococcus mutans, 99.441% efficacy against Streptococcus mitis, 99.416% efficacy against Streptococcus aureus, and 99.233% efficacy against Lactobacillus spp. Conclusion. Integrating cerium oxide nanoparticles as fillers into dental composite resin can be promising in terms of antibacterial activity, provided furthermore study has to be conducted to examine other properties. Clinical Significance. Previous studies attempted adding CeO2 nanoparticles into acrylic resins that showed improvement in mechanical properties, but literature is nil on the dental composite resin and cerium oxide nanoparticles. This study demonstrates the development of an experimental antibacterial dental composite resin that can resolve most of the problems related to secondary caries around dental composite restorations.